Upaya Meningkatkan Hasil Belajar Siswa Melalui Model Team Games Tournament Pada Mata Pelajaran Matematika Materi Bilangan Cacah Kelas V - Kintan Prigina Wuriasih; Muhammad Soleh Hapudin (Universitas Pakuan, 2026)
Efforts to Improve Student Learning Outcomes through the Team Games Tournament Model in Mathematics Subject Class Number Material This study aims to improve the mathematics learning outcomes of class VB students of SDN Penggilingan 01 on the topic of whole numbers through the application of the Team Games Tournament (TGT) learning model. The initial problem found was that many students still had difficulty understanding the basic concepts of whole numbers and showed little activity during the learning process. This study applied the Classroom Action Research (CAR) method which was carried out in two cycles, each cycle going through the stages of planning, implementation, observation, and reflection. Data collection was carried out through learning outcome tests, observation sheets of teacher and student activities, and documentation. The results of the study showed a very significant increase in student learning outcomes after the application of the TGT model. In cycle I, the number of students who completed was 15 people or 47%. This percentage increased to 26 students or 81% in cycle II, resulting in an increase of 34%. In addition, teacher activity also experienced quite significant development, from 68% in cycle I to 92% in cycle II. Student activity also improved, rising from 63% in Cycle I to 84% in Cycle II, indicating a more effective and conducive learning process. Therefore, it can be concluded that the TGT model has been proven to improve student learning outcomes and activity in mathematics. This model successfully creates a more lively, engaging, and competitive learning environment, and is able to motivate student activity throughout the entire learning process.